Management, Control And Governance Of Hawala Networks In The Gulf Cooperation Council Region - Sharif, Khurram; Mahama, Habib; Farooqi, Nauman (Asian Academy of Management (AAM), 2016)
Prior research has focused on the transactional aspects of the Hawala Networks (i.e. Invisible Funds Transfer Networks). However, little is known about the structure of this networked "organisation" especially about its governance and management control systems. Clanbased Organisations and Actor Network Theories were utilised to provide the theoretical base on which a research farmework was built. In total, 20 indepth interviews were conducted with Hawaldars (Hawala service providers) using a semi-structured questionnaire. As the study focused on the Gulf Cooperation Council region, data were collected from Qatar, UAE and Kuwait. The data indicated that there were no formal governance and management control systems in place for managing Hawala Networks (HNets); there were no explicit formal processes and mechanisms for evaluating performance and there was no formal performance measurement and tracking system in place to provide the information about network functionality. Results also showed that trust acted as the most important control mechanism impacting the efciency, eﬀectiveness and the relatively lower transaction costs associated with HNets operations